Construction of Knowledge Test to Measure the Knowledge on Recommended Groundnut Production Practices - R, Sureshverma; Samuel, G; Sreenivasa Rao, I; Sagar, Vidya; chary, Srinivasa (Journal of Extension Education, 2019)
The non-availability of a standardized scale to measure the farmers’ knowledge level influenced the researchers to construct a test for measuring the knowledge on recommended groundnut production package of practices. Pertinent items were collected covering all aspects from the crop production guide developed by the Department of Agriculture, Govt. of Tamil Nadu & Tamil Nadu Agricultural University. After getting jury opinion on the items, test index of item difficulty, index of item discrimination and point biserial correlation for the items were worked out. All these were taken in to account to arrive at the final scale. While administrating the knowledge test a respondent was given one mark for each correct answer and zero for wrong answer. Eleven (11) items were finally selected from a total of fifty five (55) items.